Serum glial cell line-derived neurotrophic factor (GDNF) a potential biomarker of executive function in Parkinson’s disease - Tong, Shu-Yan; Wang, Rui-Wen; Li, Qian; Liu, Yi; Yao, Xiao-Yan; Geng, De-Qin; Gao, Dian-Shuai; Ren, Chao (Frontiers in Neuroscience, 2023)
Objective Evidence shows that the impairment of executive function (EF) is mainly attributed to the degeneration of frontal-striatal dopamine pathway. Glial cell line-derived neurotrophic factor (GDNF), as the strongest protective neurotrophic factor for dopaminergic neurons (DANs), may play a role in EF to some extent. This study mainly explored the correlation between serum GDNF concentration and EF performance in Parkinson’s disease (PD). Methods This study recruited 45 healthy volunteers (health control, HC) and 105 PD patients, including 44 with mild cognitive impairment (PD-MCI), 20 with dementia (PD-D), and 20 with normal cognitive function (PD-N). Neuropsychological tests were performed to evaluate EF (working memory, inhibitory control, and cognitive flexibility), attention, language, memory, and visuospatial function. All subjects were tested for serum GDNF and homovanillic acid (HVA) levels by ELISA and LC-ESI-MS/MS, respectively. Results PD-MCI patients showed impairments in the trail making test (TMT) A (TMT-A), TMT-B, clock drawing test (CDT) and semantic fluency test (SFT), whereas PD-D patients performed worse in most EF tests. With the deterioration of cognitive function, the concentration of serum GDNF and HVA in PD patients decreased. In the PD group, the serum GDNF and HVA levels were negatively correlated with TMT-A (rGDNF = −0.304, P < 0.01; rHVA = −0.334, P < 0.01) and TMT-B (rGDNF = −0.329, P < 0.01; rHVA = −0.323, P < 0.01) scores. Serum GDNF levels were positively correlated with auditory verbal learning test (AVLT-H) (r = 0.252, P < 0.05) and SFT (r = 0.275, P < 0.05) scores. Serum HVA levels showed a positively correlation with digit span test (DST) (r = 0.277, P < 0.01) scores. Stepwise linear regression analysis suggested that serum GDNF and HVA concentrations and UPDRS-III were the influence factors of TMT-A and TMT-B performances in PD patients. Conclusion The decrease of serum GDNF concentration in PD patients was associated with impaired inhibitory control, cognitive flexibility, and attention performances. The changes of GDNF and HVA might synergistically participate in the occurrence and development of executive dysfunction in PD patients.